2004
DOI: 10.1152/ajprenal.00263.2003
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of erythrocyte phosphatidylserine exposure by urea and Cl

Abstract: Osmotic shock by addition of sucrose to the medium stimulates erythrocyte sphingomyelinase with subsequent ceramide formation and triggers Ca(2+) entry through stimulation of cation channels. Both ceramide and Ca(2+) activate an erythrocyte scramblase, leading to breakdown of phosphatidylserine asymmetry, a typical feature of apoptosis. Because erythrocytes are regularly exposed to osmotic shock during passage of kidney medulla, the present study explored the influence of NaCl and urea on erythrocyte phosphati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 63 publications
(70 reference statements)
2
46
0
Order By: Relevance
“…Moreover, those erythrocytes may bind to receptors in the vascular wall and thus impede microcirculation (4,5,24,47,50,51). Along those lines, we observed enhanced trapping of erythrocytes in renal medulla after ischemia of the mouse kidney (34). Phosphatidylserine-exposing cells may further participate in hemostasis (4,7,39,47,54).…”
Section: Discussionmentioning
confidence: 78%
“…Moreover, those erythrocytes may bind to receptors in the vascular wall and thus impede microcirculation (4,5,24,47,50,51). Along those lines, we observed enhanced trapping of erythrocytes in renal medulla after ischemia of the mouse kidney (34). Phosphatidylserine-exposing cells may further participate in hemostasis (4,7,39,47,54).…”
Section: Discussionmentioning
confidence: 78%
“…On the contrary, urea protects erythrocytes against hyperosmotic shock, an effect proven to be due to direct inhibition of erythrocyte sphingomyelinase (Lang et al, 2004b). Accordingly, blocking the sphingomyelinase with 600 mM of urea blunted the effect of PAF on phosphatidylserine exposure.…”
Section: Discussionmentioning
confidence: 97%
“…We have recently shown that addition of 600 mM urea inhibits hyperosmotic-shock-induced ceramide formation by interfering with sphingomyelinase activity (Lang et al, 2004b). We thus used urea to demonstrate the link between PAF-induced ceramide formation and PAF-induced phosphatidylserine exposure.…”
Section: Journal Of Cell Science 118 (6)mentioning
confidence: 99%
“…Nevertheless, it is noteworthy that during acute renal failure erythrocytes may be trapped in renal medulla. 51,52 The subsequent erythrocyte 'apoptosis' may then contribute to the derangement of microcirculation. Beyond that any erythrocyte disorder facilitating erythrocyte shrinkage, such as sickle cell disease, 28,53 thalassemia 54 or iron deficiency 55 could, to the extent as it leads to activation of the cell volume regulatory cation channels, trigger premature 'apoptosis' and thus accelerate erythrocyte death.…”
Section: -43mentioning
confidence: 99%